Implementation of interprofessional education in community setting - Fatikhu Yatuni Asmara; Saekhol Bakri; Dian Puspita Dewi; Diana Nur Afifah; Tri Nur Kristina (Journal of Community Empowerment for Health, 2019)
Community health problem(s) needs to be solved collaboratively among the health care team. Interprofessional Education (IPE) is implemented to facilitate health students to collaborate before they join in the working world. The purpose of this study was to identify the experience of students, lecturers, and family members in the implementation of IPE in a community setting. All (465) sixth semester medical, nursing, and nutrition students in the Faculty of Medicine Universitas Diponegoro participated in the IPE program. Each small group contains 4-5 students who worked together in the community setting to identify family health problems, implement interventions, and evaluate the results. Focus Group Discussion (FGD) was conducted to evaluate the implementation. Twenty-four medical, nursing, and nutrition students, eight lecturers, and five family members were involved in this study. FGD was conducted separately among groups. The implementation is divided into four phases, namely, preparation, process, evaluation, and benefit. Unclear competencies and roles-responsibilities of each student in the program was the most problem faced during preparation, while obstacles during the process were difficult to set a schedule among team members. Conducting an objective assessment of both methods and tools needs to be concerned in the evaluation phase. However, students, lecturers, and family members appreciated the program and preferred to sustain the program. IPE can be implemented in a community setting to solve health problems and it can facilitate students to collaborate in a team, but it needs to be settled including preparation, process, and evaluation.